Ru, Pd doped WO3 nanomaterials: a synergistic effect of noble metals to enhance the acetone response properties - Kodam, Pavan M.; Ghadage, Pandurang A.; Nadargi, Digambar Y.; Shinde, K. P.; Mulla, Imtiaz S.; Park, J. S.; Suryavanshi, Sharad S. (Ceramics International, 2022)
Noble metals (NMs) have an enormous impact on the intrinsic properties of the metal oxides. We report the synergistic effect of Ruthenium (Ru) and Palladium (Pd) noble metals on the enhancement of gas sensing properties of pure tungsten oxide (WO3). The gas sensing material is synthesized by simple and straight forward precipitation route, and its physico-chemical analyses are determined using XRD, FESEM, TEM/HRTEM, FFT, UV-Vis, XPS, EDAX, and BET measurements. Use of the developed material as a gas sensor is evaluated using several target gases (oxidizing as well as reducing), with acetone showing the best selectivity. The noble metal doping and hence catalytic action improved the gas response qualities. The synergistic effect of Ru and Pd on WO3 gas response properties are identified, where the effect is 99.80% sensitivity, and lower response/recovery time (10 s and 2 min) at 300 degrees C operating temperature. Nonetheless, the sensors displayed better gas sensing properties even at lower operating temperatures ranging from 200 to 275 degrees C. In addition, the synergistic effect has displayed the dramatic enhancement in the sensitivity to 76.44% at barely 10 ppm acetone concentration. This particular result will undoubtedly be helpful for diagnostic purpose of diabetic patients, and a strong candidate for prospective gas sensing applications, particularly acetone.
Keywords: Acetone vapours; Precipitation route; Ru -Pd doping; synergistic effect; WO3

Green synthesis of GO-loaded Ag/ZnO nanocomposites for methyl orange degradation - Nadargi, Digambar Y.; Nadargi, Jyoti D.; Tamboli, Mohaseen S.; Tamboli, Asiya M.; Mulla, Imitaz S.; Umar, Ahmad; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (Journal of Materials Science-Materials in Electronics, 2023)
Nature is a perfect laboratory for creating novel nanomaterials for a variety of applications. A robust green synthesis approach to GO-loaded Ag/ZnO nanocomposite materials using medicinal plant extraction and their potential application in methyl orange dye degradation are reported. The straightforward technique employs zinc and silver nitrate precursors in an aqueous solution of medicinal plant extract, causing the precipitation process. Prior to photocatalytic investigations, the physico-chemical properties of the material are analysed using TG-DTA, XRD, FE-SEM, TEM, EDAX and BET. The developed material showcase hexagonal wurtzite structure of ZnO, with face-centered-cubic phase of Ag and AgCl. All the samples exhibit aggregated, irregular rounded grains, as expected in the precipitation synthesis process. Pristine ZnO showed 15.5% degradation efficiency towards methyl orange, which was further improved by doping Ag from 0.5 to 2 mol%. The catalyst with 1 mol% Ag doping resulted in the better photocatalytic activity (26.30%), which has again improved by loading the GO (27.46%). The outcome of this study provides the new insights to GO-loaded Ag/ZnO nanocomposites by green synthesis route, in view of photocatalytic applications.

La-Fe-O perovskite based gas sensors: recent advances and future challenges - Patil, Suraj S.; Babar, Bapuso M.; Nadargi, Digambar Y.; Shaikh, Faiyyaj I.; Nadargi, Jyoti D.; Sankapal, Babasaheb R.; Mulla, Imtiaz S.; Tamboli, Mohaseen S.; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (ACS OMEGA, 2024)
Keywords: ASSISTED SYNTHESIS; ETHANOL SENSING CHARACTERISTICS; LAFEO3 NANOPARTICLES

Surfactant-assisted tungsten oxide for enhanced acetone sensing and solar-driven photocatalysis: exploring the role of surfactants - Patil, Abhijeet P.; Patil, Suraj S.; Tamboli, Mohaseen S.; Damkale, Shubhangi R.; Nadargi, Digambar Y.; Nadargi, Jyoti D.; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (RSC Advances, 2025)
Surfactants play a pivotal role in the kinetics of nucleation and accretion of nanoparticles in such a way that they serve as a template for the development of nanostructures, consequently influencing the morphology, dimensions, and other surface properties. Herein, we report the influence of cationic and anionic surfactants (CTAB, SDS, PVP and HMT) on the development of pristine WO3 nanostructures and their impact on gas sensing and photocatalytic properties of WO3. The various surfactant-assisted WO3 nanostructures were synthesized via a straightforward hydrothermal route and systematically analyzed using XRD, FESEM-EDAX, TEM/HRTEM, XPS, UV-Vis, and BET measurements. Gas sensing properties of various oxidizing and reducing gases revealed superior selectivity towards acetone. Among the various surfactant-assisted WO3, CTAB/WO3 exhibited an excellent response of 84.84% towards 100 ppm acetone at an optimal operating temperature of 300 degrees C. The CTAB/WO3 sensor exhibited a linear response to acetone at lower concentrations, showing a 4.8% response at 0.8 ppm, which delineates the threshold between healthy and diabetic breath acetone levels. At 1.8 ppm, the sensor recorded 8.1% response, aligning with diabetes values reported by National Institute for Occupational Safety and Health (NIOSH). Moreover, photocatalytic performance evaluations demonstrated a methylene blue degradation efficiency of 47.19% under natural solar irradiation. This work will motivate researchers in developing high performance acetone gas sensors and photocatalytic dye-degradation by the integration of appropriate surfactants in WO3 nanostructures.